Karakteristik Mazmur Pujian - Darto Sachius (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2021)
The study is titled characteristics Psalm of Praise. This study will seek and discover the characteristics and principles of psalm praise in the Book of Psalms. To discover the characteristics of the Praise Psalm used qualitative rather than experimental research methods. This qualitative method can also be used for reflective speculators. With four steps: analyzing the passage according to its elements, the second step is to recognize the language style of poetry and stories that are historical, the third reveals the original meaning of Hebrew poetry, the fourth looks for the characteristics of the Hebrew satra of the author's motives and goals. So that preserved by this method can be formulated characteristics from the Psalm of Praise. There are three important things to remember in the Psalm of praise is, first the Psalm of praise begins with an invitation to worship The Lord, The second psalm of praise continues by giving a description of the reasons why God is worthy of praise. Third is the psalm praise usually includes and sometimes ends with a further invitation to praise God therefore the proper title is the characteristics Psalm of Praise so that the awkwardness of distinguishing the interpretation of different types of psalm can be well cleared.